New and rare tropical and subtropical fishes from northern New Zealand - Malcolm P. Francis; Craig J. Worthington; Peter Saul; Kendall D. Clements (New Zealand Journal of Marine and Freshwater Research, 1999)
Five fish species (Platax teira, Abudefduf vaigiensis, Chromis flavomaculata, Coris dorsomacula , and Aluterus scriptus) are recorded from New Zealand for the first time, and five species (Forcipiger flavissimus, Chromis vanderbilti, Chrysiptera rapanui, Parma kermadecensis , and Thalassoma lutescens) are newly recorded from mainland New Zealand. Five other species that have been reported previously in the popular press, or by name only, are confirmed as members of the New Zealand fauna (Carcharhinus longimanus, Etelis carbunculus, Istiophorus platypterus, Acanthocybium solandri , and Aseraggodes bahamondei) . New observations of 20 previously reported tropical and subtropical species are also presented. Many of the fishes were observed in autumn 1996, 1998, and 1999, indicating recruitment or immigration when sea surface temperature (SST) was higher than average. Major influxes of tropical and subtropical fishes apparently occur during warm summers, although some warm periods were not accompanied by influxes, and a few tropical and subtropical fishes arrived when SST was average or below average. The most likely upstream source of reef fish larvae is Norfolk Island, and the principal transport mechanism is probably the East Auckland Current. The discovery in north‐eastern New Zealand of single individuals of Parma kermadecensis and the yellow form of Chrysiptera rapanui , both previously regarded as Kermadec Islands endemics, provides evidence for occasional larval transport from the Kermadecs to north‐eastern New Zealand.